2006
DOI: 10.1089/end.2006.20.215
|View full text |Cite
|
Sign up to set email alerts
|

PlasmaKinetic Superpulse Transurethral Resection versus Conventional Transurethral Resection of Prostate

Abstract: The PK Superpulse system provides faster removal of tissue in a bloodless field with better views and a safer environment of saline irrigation with efficacy comparable to that of conventional TURP. However, further randomized trials with extended follow-up may be needed to better define the role of the PK Superpulse system in treating patients with symptomatic BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 17 publications
0
43
2
7
Order By: Relevance
“…Michielsen et al have reported significantly longer operating times with bipolar resection (12). Recent studies have shown shorter operating times, less blood loss and shorter periods of irrigation and catheterization with bipolar resection (13,14). Improvement in Qmax in our study was significantly higher with the bipolar group although IPSS was comparable in both the groups.…”
Section: Commentscontrasting
confidence: 52%
“…Michielsen et al have reported significantly longer operating times with bipolar resection (12). Recent studies have shown shorter operating times, less blood loss and shorter periods of irrigation and catheterization with bipolar resection (13,14). Improvement in Qmax in our study was significantly higher with the bipolar group although IPSS was comparable in both the groups.…”
Section: Commentscontrasting
confidence: 52%
“…However, they reported no advantages of P-TURP in terms of intra-and post-operative bleeding, the duration of hospitalization, operation time and late complications. Patankar et al [8] emphasized that P-TURP enabled faster tissue resection in a bloodless area and a safer surgery using saline irrigation. Bhansali et al [9] stated that P-TURP could be used safely and effectively for the resection of a large gland (>60 g) based on a minimum of 9 months follow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar group showed mean post-op Q-max 18.6 mL/sec, P value > 0.05 which is not statistically significant. Patankar et al (11) in his study had comparable improvement in Q-max in both groups (19.16 and 20.67 mL/sec) postoperatively. However, late followup of all our patients are required to evaluate a long-term outcome of both our surgical groups.…”
Section: Discussionmentioning
confidence: 65%
“…However, none of the patient in either group required blood transfusion. Patankar et al (11) in his study found significant blood loss among patients undergoing monopolar TURP (282.67 mL) as compared to those undergoing bipolar TURP (140.6 mL). Singhania et al (7) in his study showed statistically significant haemoglobin drop (0.97 gm%, p value < 0.005) as compared to bipolar group which showed small drop in haemoglobin (0.55 gm%, p value = 0.014).…”
Section: Discussionmentioning
confidence: 90%